2019
DOI: 10.2147/cmar.s191352
|View full text |Cite
|
Sign up to set email alerts
|

<p>Apolipoprotein A1 and B as risk factors for development of intraocular metastasis in patients with breast cancer</p>

Abstract: Objective: Breast cancer is the most common primary lesion resulting in intraocular metastasis (IOM). In this study, we investigated the differences between breast cancer patients with and without IOM, and clarified the risk factors for IOM in patients with breast cancer. Methods: A total of 2,381 patients with breast cancer were included in this study from January 2005 to December 2017. The chi-square test and Student’s t -test were applied to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Upon diagnosing IDC, the apoA-I level is inversely associated with tumor size [21]. Liu et al demonstrated that apoA-I is of higher reliability in distinguishing whether patients with BC have intraocular metastases, which provides direct evidence to support the claim that apoA-I is involved in BC metastasis [65]. As we described above, higher apoA-I levels in plasma tend to decrease BC risk.…”
Section: Apoa-i Apoj and Bcmentioning
confidence: 59%
See 1 more Smart Citation
“…Upon diagnosing IDC, the apoA-I level is inversely associated with tumor size [21]. Liu et al demonstrated that apoA-I is of higher reliability in distinguishing whether patients with BC have intraocular metastases, which provides direct evidence to support the claim that apoA-I is involved in BC metastasis [65]. As we described above, higher apoA-I levels in plasma tend to decrease BC risk.…”
Section: Apoa-i Apoj and Bcmentioning
confidence: 59%
“…The investigation into the connections between apoB gene polymorphisms and BC risk reported by Liu et al concluded that polymorphisms, such as 12,669 GA and 7673 CT, significantly increase the risk of this tumor, particularly in women undergoing menopause [72]. Once breast carcinoma develops intraocular metastasis, apoB functions as a risk factor like apoA-I [65]. Whether the immediate role of apoB in mammary tissues is similar to that of apoA-I needs to be determined in the future.…”
Section: Apob Apoc-i Apom and Bcmentioning
confidence: 99%
“…Serum lipids are risk factors of numerous types of cancers, and has crucial roles in cancer metabolism. 37,38 Apolipoprotein B (APOB) as a lipid binding protein is a main component of chylomicrons and low-density lipoproteins (LDL). 39 ApoB-100, as an isoform of APOB synthesized exclusively in the liver, is required for the production of triglyceride-rich VLDL.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that APOB was implicated in the progression and recurrence of some kinds of malignant tumors. A recent study reported 18 that APOB was an independent risk factor for intraocular metastasis in patients with breast cancer, and APOB could be utilized as a serum biomarker to identify intraocular metastasis from non-intraocular metastasis. Besides, a comprehensive network analysis revealed that APOB might be a tumor suppressor gene, and aberrant expression of APOB was markedly associated with unfavorable clinical outcome in patients with liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] However, recent studies have suggested that APOB also plays an important role in the occurrence and progression of various tumors, including hepatocellular carcinoma, 15 kidney renal clear cell carcinoma, 16 nonesophageal squamous cell carcinoma, 17 and breast cancer. 18 However, no study has specifically investigated the prognostic role of APOB in patients with glioma. Importantly, based on the bioinformatic analysis, we found that APOB mRNA expression was negatively regulated by DNA promoter methylation in patients with LGG.…”
Section: Introductionmentioning
confidence: 99%